2020
DOI: 10.15252/embr.201949210
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted hypothalamic CRH neuron responsiveness contributes to diet‐induced obesity

Abstract: The current obesity epidemic mainly results from high-fat highcaloric diet (HFD) feeding and may also be contributed by chronic stress; however, the neural basis underlying stress-related dietinduced obesity remains unknown. Corticotropin-releasing hormone (CRH) neurons in the paraventricular hypothalamus (PVH), a known body weight-regulating region, represent one key group of stress-responsive neurons. Here, we found that HFD feeding blunted PVH CRH neuron response to nutritional challenges as well as stress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…Diet is also capable of remodeling circadian rhythms behaviorally, transcriptionally, and metabolically [ 22 , 260 , 272 , 273 ]. For example, feeding mice a ketogenic diet or overexpressing the FGF21 (whose production is stimulated by a ketogenic diet) augments locomotion during the daytime and results in a phase advance in mice [ 183 ].…”
Section: The Role Of Intrinsic Clocks Of the Hypothalamus In Obesimentioning
confidence: 99%
See 1 more Smart Citation
“…Diet is also capable of remodeling circadian rhythms behaviorally, transcriptionally, and metabolically [ 22 , 260 , 272 , 273 ]. For example, feeding mice a ketogenic diet or overexpressing the FGF21 (whose production is stimulated by a ketogenic diet) augments locomotion during the daytime and results in a phase advance in mice [ 183 ].…”
Section: The Role Of Intrinsic Clocks Of the Hypothalamus In Obesimentioning
confidence: 99%
“…For example, feeding mice a ketogenic diet or overexpressing the FGF21 (whose production is stimulated by a ketogenic diet) augments locomotion during the daytime and results in a phase advance in mice [ 183 ]. Mice placed on standard HFD have a profound reorganization of their circadian gene expression and metabolite production, in several metabolic tissues, including liver, adipose tissue, and the CNS [ 22 , 272 , 273 ]. However, hypothalamic PER2::LUC rhythms in the SCN, DMH or ARC appear unaltered under HFD [ 91 ].…”
Section: The Role Of Intrinsic Clocks Of the Hypothalamus In Obesimentioning
confidence: 99%
“…The exception was a reduced energy expenditure exhibited by CRH GHR KO females. High-fat/high-caloric diet disturbs the activity of PVH CRH neurons, leading to decreased energy expenditure [ 74 ]. Intriguingly, it is unknown why the low energy expenditure was observed only in CRH GHR KO female mice.…”
Section: Discussionmentioning
confidence: 99%
“…It was recently reported that fasting-induced activation of AMP-activated kinase (AMPK) causes increased activity of PVH CRH neurons, which contributes to a preference for a high-carbohydrate diet (nutrition) over a HFD (palatability) under fasting conditions 64 . A more recent study demonstrated that HFD feeding blunted the responsiveness of PVH CRH neurons and that mice with blunted PVH CRH neuronal responsiveness were more likely to develop HFD-induced obesity 65 . Overall, these studies suggest that PVH CRH neurons may participate in the fine tuning of food intake rather than control food intake per se.…”
Section: Role Of the Hpa Axis And Crh Neuronsmentioning
confidence: 99%